Long‐term electrical performance of Attain Performa quadripolar left ventricular leads with all steroid‐eluting electrodes: Results from a large worldwide clinical trial. Issue 8 (5th July 2018) - Lin, Albert C.; Biffi, Mauro; Exner, Derek V.; Johnson, W. Ben; Gras, Daniel; Hussin, Azlan; Singh, Balbir; Yang, Zhongping; Hine, Douglas; Li, Shelby; Crossley, George H.
Abstract: Background: Steroid‐eluting (SE) electrodes suppress local inflammation and lower pacing capture thresholds (PCT); however, their effectiveness on quadripolar left ventricular (LV) leads in the cardiac vein is not fully studied. We evaluated the effectiveness of SE on all four LV pacing electrodes in human subjects enrolled in the Medtronic Attain® Performa™ quadripolar LV lead study. Methods: A total of 1, 097 subjects were included in this evaluation. At each follow‐up visit (1, 3, 6, and 12 months), LV PCT and pacing impedance were measured using either manual or automated testing methods. Summary statistics for PCT and impedance values were obtained for implant and each scheduled follow‐up visit for all lead models. Results: Average extended bipolar (LV electrode to right ventricular Coil) PCTs for the four LV SE pacing electrodes (LV1, LV2, LV3, and LV4) on the three shapes of the quadripolar LV leads were 1.06 ± 0.97 V, 1.38 ± 1.26 V, 1.51 ± 1.33 V, and 2.25 ± 1.63 V, respectively, at 0.5‐ms pulse width. PCTs remained low and stable throughout the 12‐month follow‐up period. Conclusion: This clinical trial demonstrated that SE on all LV pacing electrodes is associated with low and stable PCTs for all quadripolar LV lead electrodes, resulting in multiple viable vectors for LV pacing. The large number of available vectors facilitates basal pacing, avoidance of PNS, and potentially prolongs generator longevity due to lower PCTs.